A Bentall Is Not a Bentall Is Not a Bentall: The Evolution of Aortic Root Surgery - Maddalo, Scott (Aorta (Stamford), 2014)
Background: Aortic root pathology had been a known entity with a progressive and catastrophic course, long before the methods to surgically address them were first developed. Once reliable cardiopulmonary bypass was established, surgeons were able to pioneer new operative techniques, and in the half-century to follow, countless modifications and refinements have provided today's surgeons with the surgical approaches that are currently at their disposal. History: Denton Cooley and Michael De Bakey reported the first successful surgical intervention for aneurysms involving the ascending aorta in 1956. Nearly a decade later, Hugh Bentall described his modification, and provided a name that would leave a lasting mark on aneurysmal surgery. In the decades to follow, numerous innovative surgeons improved on these original procedures to allow for a more reliable and consistent operation. Further, Tirone David and Sir Magdi Yacoub each described their methods to repair the aortic root while preserving the valve, thus providing their patients with freedom from a prosthetic or mechanical valve and improved quality of life. Conclusions: The development of surgical techniques required to successfully care for patients with pathology of the aortic root has evolved considerably since Cooley and De Bakey's original report. Although it is common to hear aortic root replacement referred to as a “Bentall,” the methods currently employed have gone through considerable evolution, such that the techniques of today should not be referred to as a Bentall.